The dom and gift among midwives from Amapá: an ethnographic approach - Cardoso, Marcus André de Souza; Nascimento, Raysa (Saúde e Sociedade, 2019)
This article studies the world conceptions and practices of traditional midwives who live and work in Santana (Amapá, Brazil). Based on an ethnographic fieldwork including semi-structured interviews, we present how these women perceive their craft, highlighting the centrality of the category dom and the notion of divine in this universe. We also discuss the symbolic dimension of the relationships established between the midwives, the pregnant women and the entity known by them as God. In this regard, the obligations associated to the non-compulsory debts in the giving, receiving and returning cycle, pointed out by most studies on traditional midwives, are not restricted to the relation between the patient’s family and the midwife. According to the local conception, the most relevant relations of obligation associated to the dom for their craft are those established between humans and God. The counter-gift is accomplished through patient care, but as a sort of obligation towards God. Assisting the women who seek midwives is, thus, understood as the adequate means to settle the debt with this divine entity.